Resposta :
Resposta:
Explicação passo a passo:
[tex]a_{1} =1[/tex]
[tex]q=3[/tex]
[tex]a_{n} =729[/tex]
[tex]a_{n} =a_{1} .q^{(n-1)}[/tex]
[tex]729=1.3^{(n-1)}[/tex]
[tex]3^{(n-1)} =729[/tex]
[tex]3^{(n-1)} =3^{6}[/tex]
[tex]n-1=6[/tex]
[tex]n=6+1[/tex]
[tex]n=7[/tex]
[tex]S_{n} =\frac{a_{1}.(q^{n}-1) }{q-1}[/tex]
[tex]S_{7} =\frac{a_{1}.(q^{7}-1) }{q-1}[/tex]
[tex]S_{7} =\frac{1.(3^{7}-1) }{3-1}[/tex]
[tex]S_{7}= \frac{3^{7}-1 }{2}[/tex]
[tex]S_{7}=\frac{2187-1}{2}[/tex]
[tex]S_{7}=\frac{2186}{2}[/tex]
[tex]S_{7}= 1093[/tex]
[tex]Resposta:\:1093[/tex]